Generalized Contractions and Fixed Point Results in Spaces with Altering Metrics - Adrian Nicolae Branga; Ion Marian Olaru (Mathematics, 2022)
In this paper, we have provided some fixed point results for self-mappings fulfilling generalized contractive conditions on altered metric spaces. In addition, some applications of the main results to continuous data dependence of the fixed points of operators defined on these spaces were shown.